Torque Ripple Minimization and Performance Investigation of an In-Wheel Permanent Magnet Motor - Mansouri, A.; Hafedh, T. (Engineering, Technology & Applied Science Research, 2016)
Recently, electric vehicle motoring has become a topic of interest, due to the several problems caused by thermal engines such as pollution and high oil prices. Thus, electric motors are increasingly applied in vehicle’ applications and relevant research about these motors and their applications has been performed. Of particular interest are the improvements regarding torque production capability, the minimization of torque ripple and iron losses. The present work deals with the optimum design and the performance investigation of an outer rotor permanent magnet motor for in-wheel electric vehicle application. At first, and in order to find the optimum motor design, a new based particle-swarm multi-objective optimization procedure is applied. Three objective functions are used: efficiency maximization, weight and ripple torque minimization. Secondly, the effects of the permanent magnets segmentation, the stator slots opening, and the separation of adjacent magnets by air are outlined. The aim of the paper is the design of a topology with smooth output torque, low ripple torque, low iron losses and mechanical robustness.